Congenital toxoplasmosis: An uncommon disease in Thailand - Krisana Pengsaa (2018)
© W. S. Maney & Son Ltd 2015. Background: The seroprevalence of toxoplasma antibodies in pregnant women and the prevalence of congenital infection differ widely between countries. A few cases of congenital toxoplasmosis diagnosed after the neonatal period, with long-term sequelae, have been reported in Thailand. No data on the prevalence of congenital toxoplasmosis have been documented and no screening for toxoplasmosis during pregnancy has been undertaken in Thailand.Subjects and Methods: A questionnaire enquiring about cases of congenital toxoplasmosis during 1995-2013 was distributed to paediatricians in referral and university hospitals in Thailand and the responses were analysed. Specific toxoplasma IgM antibody and clinical features were used for diagnosis.Results: There were 20 cases - 13 most likely and seven suspected cases of congenital toxoplasmosis. Most patients had systemic manifestations, but only 25% of diagnosed patients exhibited the classic triad of hydrocephalus, cerebral calcification and chorioretinitis. One of the five deceased patients lived beyond the age of 13 years and died of a pulmonary infection. All 15 surviving cases developed deafness, visual impairment or developmental delay.Conclusions: Twenty cases of congenital toxoplasmosis are reported. Delayed diagnosis and treatment resulted in a poor outcome. The prevention of toxoplasmosis in pregnant women and prompt diagnosis and appropriate treatment of congenital toxoplasmosis should be a priority in order to prevent a poor outcome in infected children.